International Monetary Fund Annual Report 1974. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1974)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1974. The report highlights that in mid-1974, the world economy was in the throes of a virulent and widespread inflation, a deceleration of economic growth in reaction to the preceding high rate of expansion, and a massive disequilibrium in international payments. The average annual rate of inflation in industrial countries, already 7 percent in 1973, reached 12 percent (in terms of gross national product deflators) in the first half of 1974.